EXTRACTION AND VERIFICATION OF LOAD SPECTRUM OF STEERING KNUCLE BASED ON VIRTUAL ITERATION METHOD - DONG GuoJiang; WANG Wei; DU Fei; LANG YuLing (Jixie qiangdu)
The load spectrum of automotive chassis components is the key factor to analyze the fatigue,reliability and durability of components.However,it still needs further practice and direct verification in the process of extracting road load spectrum and the key link processing,as well as error evaluation,etc.Based on this,this paper takes a certain type of automobile steering knuckle as the research object,established rigid-flexible coupling multi-body dynamic simulation model of the whole vehicle,and calibrated it through the test site reinforced the road test,the error between the monitoring signal of the measured key points and the iterative simulation is less than 30%,which verifies the response accuracy of the vehicle multi-body model; The load spectrum of road surface strengthened by endurance test of real vehicle was collected,and the load spectrum of steering knuckle connection points was obtained by simulation decomposition using virtual iteration method; Take typical working conditions of stone road Cand washboard road as examples,the inertia release method was used to solve the time-domain strain field of steering knuckle by using the load spectrum of connection points as input excitation,and time-domain strain curves of monitoring points are obtained,the relative error of the analysis of measured signals is less than 20%,which meets the accuracy requirements of the subsequent use of the load spectrum.The results show that strain calibration method is a direct verification of the effect of virtual iteration load spectrum extraction,which proves the feasibility and accuracy of the load spectrum extraction technical route,and provides a reference for the development of automobile chassis parts and fatigue durability analysis and verification.